Comparative genomic analysis of trypanosomatid protists illuminates an extensive change in the nuclear genetic code - Záhonová, Kristína; Füssy, Zoltán; Albanaz, Amanda T S; Butenko, Anzhelika; Kachale, Ambar; Kraeva, Natalya; Galan, Arnau; Zakharova, Alexandra; Stojanova, Bojana; Votýpka, Jan; Kostygov, Alexei Y; Spodareva, Viktoria V; et al. (mBio, 2025)
UNLABELLED: Trypanosomatids are among the most extensively studied protists due to their parasitic interactions with insects, vertebrates, and plants. Recently, Blastocrithidia nonstop was found to depart from the canonical genetic code, with all three stop codons reassigned to encode amino acids (UAR for glutamate and UGA for tryptophan), and UAA having dual meaning also as a termination signal (glutamate and stop). To explore features linked to this phenomenon, we analyzed the genomes of four Blastocrithidia and four Obscuromonas species, the latter representing a sister group employing the canonical genetic code. We found that all Blastocrithidia species encode cognate tRNAs for UAR codons, possess a distinct 4 bp anticodon stem tRNATrpCCA decoding UGA, and utilize UAA as the only stop codon. The distribution of in-frame reassigned codons is consistently non-random, suggesting a translational burden avoided in highly expressed genes. Frame-specific enrichment of UAA codons immediately following the genuine UAA stop codon, not observed in Obscuromonas, points to a specific mode of termination. All Blastocrithidia species possess specific mutations in eukaryotic release factor 1 and a unique acidic region following the prion-like N-terminus of eukaryotic release factor 3 that may be associated with stop codon readthrough. We infer that the common ancestor of the genus Blastocrithidia already exhibited a GC-poor genome with the non-canonical genetic code. Our comparative analysis highlights features associated with this extensive stop codon reassignment. This cascade of mutually dependent adaptations, driven by increasing AU-richness in transcripts and frequent emergence of in-frame stops, underscores the dynamic interplay between genome composition and genetic code plasticity to maintain vital functionality. IMPORTANCE: The genetic code, assigning amino acids to codons, is almost universal, yet an increasing number of its alterations keep emerging, mostly in organelles and unicellular eukaryotes. One such case is the trypanosomatid genus Blastocrithidia, where all three stop codons were reassigned to amino acids, with UAA also serving as a sole termination signal. We conducted a comparative analysis of four Blastocrithidia species, all with the same non-canonical genetic code, and their close relatives of the genus Obscuromonas, which retain the canonical code. This across-genome comparison allowed the identification of key traits associated with genetic code reassignment in Blastocrithidia. This work provides insight into the evolutionary steps, facilitating an extensive departure from the canonical genetic code that occurred independently in several eukaryotic lineages.
Keywords: Codon, Terminator; reassigned codon; Genome, Protozoan; Cell Nucleus; RNA transferová; nuclear genetic code; fylogeneze; eukaryotic release factors; tRNA structure; Phylogeny; molekulární evoluce; Evolution, Molecular; buněčné jádro; Genomics; Genetic Code; Trypanosomatina; RNA, Transfer; genetický kód; terminační kodon; genom protozoální; termination of translation; AT-rich genomes; genomika